Lymph node ratio and surgical quality are strong prognostic factors of rectal cancer: results from a single referral centre. (8th June 2016) - Leonard, D.; Remue, C.; Abbes Orabi, N.; van Maanen, A.; Danse, E.; Dragean, A.; Debetancourt, D.; Humblet, Y.; Jouret‐Mourin, A.; Maddalena, F.; Medina Benites, A.; Scalliet, P.; et al.
Abstract: Aim: Nodal stage is a strong prognostic factor of oncological outcome of rectal cancer. To compensate for the variation in total number of harvested nodes, calculation of the lymph node ratio (LNR) has been advocated. The aim of the study was to compare the impact, on the long‐term oncological outcome, of the LNR with other predictive factors, including the quality of total mesorectal excision (TME) and the state of the circumferential resection margin. Method: Consecutive patients having elective surgery for nonmetastatic rectal cancer were extracted from a prospectively maintained database. Retrospective uni‐ and multivariate analyses were performed based on patient‐, surgical‐ and tumour‐related factors. The prognostic value of the LNR on overall survival (OS) and on overall recurrence‐free survival (ORFS) was assessed and a cut‐off value was determined. Results: From 1998 to 2013, out of 456 patients, 357 with nonmetastatic disease were operated on for rectal cancer. Neoadjuvant radiochemotherapy was administered to 66.7% of the patients. The mean number of lymph nodes retrieved was 12.8 ± 8.78 per surgical specimen. A lower lymph node yield was obtained in patients who received neoadjuvant chemoradiotherapy (11.8 vs 14.2; P  = 0.014). The 5‐year ORFS was 71.8% and the 5‐year OS was 80.1%. Multivariate analysis confirmed LNR, the quality of TME and age to be independent prognostic factors of OS. LNR, age and perineural infiltration were independently associated with ORFS. Low‐ and high‐risk patients could be discriminated using an LNR cut‐off value of 0.2. Conclusion: LNR is an independent prognostic factor of OS and ORFS. In line with the principles of optimal surgical management, the quality of TME and lymph node yield are essential technical requirements.